Ocrelizumab-Induced Severe Colitis - Hsing Hwa Lee; Naveen Sritharan; Daniel Bermingham; Gabriela Strey (Case Reports in Gastrointestinal Medicine)
We report a case of severe ocrelizumab (anti-CD20 monoclonal antibody) induced colitis in a 43-year-old woman with multiple sclerosis leading to total colectomy after failing medical therapy. Histology of the colectomy was consistent with medication-induced colitis.